COVID-19: A Driver for Disruptive Innovation of the Emergency Medicine Residency Application Process - Alexis Pelletier-Bui; Doug Franzen; Liza Smith; Laura Hopson; Lucienne Lutfy-Clayton; Kendra Parekh; Mark Olaf; Tom Morrissey; David Gordon; Erin McDonough; Benjamin H. Schnapp; Mary Ann Edens; et al. (Western Journal of Emergency Medicine, 2020)
The coronavirus disease (COVID-19) pandemic has had a significant impact on undergraduate medical education with limitation of patient care activities and disruption to medical licensing examinations. In an effort to promote both safety and equity, the emergency medicine (EM) community has recommended no away rotations for EM applicants and entirely virtual interviews during this year’s residency application cycle. These changes affect the components of the EM residency application most highly regarded by program directors – Standardized Letters of Evaluation from EM rotations, board scores, and interactions during the interview. The Council of Residency Directors in Emergency Medicine Application Process Improvement Committee suggests solutions not only for the upcoming year but also to address longstanding difficulties within the process, encouraging residency programs to leverage these challenges as an opportunity for disruptive innovation.